ANALYSIS OF FINANCIAL DISTRESS IN VARIOUS INDUSTRIAL SECTOR COMPANIES LISTED ON THE BEI ​​FOR THE 2016-2021 PERIOD - Basar, Wasti Amestris; Yulazri, Yulazri (Dynamic Management Journal, 2023)
AbstractThis study aims to detect financial distress in various industrial sector companies using the Modified Altman Z-Score Model (1995). Financial distress occurs when the company is in an unhealthy state but has not yet gone bankrupt. The population used is the various industrial sector companies for the 2016-2021 period. The sample in this study were 26 companies with a research period of 6 years so as to produce 156 samples obtained by purposive sampling technique. The data analysis technique used is descriptive statistical analysis and discriminant regression analysis using the SPSS statistical test tool. The results of this study indicate that the variables of WCTA, RETA, EBITA, and BVETL have a simultaneous effect on financial distress. Partially, the variable WCTA has no effect on financial distress. While partially RETA, EBITA, BVETL affect financial distress. Keywords: Altman Z-Score Modification and Financial Distress